MENGATASI INTOLERANSI SISWA MENGGUNAKAN KONSELING BEHAVIORISTIK TEKNIK KONTRAK PERILAKU DI SMAN 2 BAE KUDUS - Nada, Via Qotrun; Hidayati, Richma; Kiswantoro, Arista (Jurnal Muria Research Guidance and Counseling (MRGC), 2024)
The aims of this study are: 1. To describe the factors that cause students at SMAN 2 Bae Kudus to have intolerance. 2. Overcoming student intolerance using behavioristic counseling with behavioral contract techniques at SMAN 2 Bae Kudus.The type of research used is guidance and counseling case studies with qualitative methods; the subjects studied were two students from SMAN 2 Bae Kudus. The methods used in this study are interviews, observation and documentation in an in-depth way so that later you can obtain accurate data about the problem under study, namely the problem of intolerance behavior. Based on the research results, it can be concluded that there are two factors that cause intolerance in students, namely internal factors and external factors. There are several factors that cause MF to behave intolerantly, namely not liking informatics lessons even with the teacher, feeling uncomfortable in class, and often talking to himself with his classmates or around his bench when the lesson is in progress. While the factors that cause JI to behave intolerantly are feeling bored with math lessons, not liking math lessons, sleeping during class, and playing on their own cellphones when lessons are in progress, Therefore, what makes MF and JI counselees behave intolerantly is not respecting and respecting others, not introspecting himself, not paying attention to and listening to his teacher, talking to himself and playing in class when lessons begin, and imposing the will of others. After carrying out individual counseling using a behavioristic approach, the counselee's behavior contract technique can eliminate his bad behavior and change it to a better one.